Rodó-de-Zárate, Maria; Jorba Grau, Marta; Foradada Villar, Mireia i Batlle Manonelles, Ares (eds.) (2017). Terra de ningú: Perspectives feministes sobre la independència - Roqueta-Fernàndez, Marta (Documents d'Anàlisi Geogràfica, 2019)
Rodó-de-Zárate, Maria; Jorba Grau, Marta; Foradada Villar, Mireia i Batlle Manonelles, Ares (eds.) (2017) Terra de ningú: Perspectives feministes sobre la independència Barcelona: Pol·len Edicions, 437 p. ISBN 978-84-16828-22-7